Effects of compressibility and surface roughness on mold filling in micro-injection molding - Nguyen Quoc Mai Phuong (2014)
Micro-injection molding has become a major process for mass production of micro-plastic parts. With a decrease in part dimensions, some factors generally ignored in classical injection molding could well become significant. This research focuses on two key factors, namely polymer melt compressibility and cavity surface roughness. Invoking 2.5D Hele-Shaw approximation for a compressible viscous flow under non-isothermal conditions, an in-house numerical model and the associated computer codes were developed. Experimental and numerical investigations were conducted on a rectangular-shaped micro-thickness cavity in various sizes, with different surface roughness on its two halves, various molding conditions, and different polymers such as COC and PP. It is shown that compressible flow should be considered in micro-mold filling as it affects the pressure and density distributions in the molded part. The compressibility and surface roughness effects become more pronounced with increasing part sizes, decreasing thickness, decreasing mold and melt temperatures. Different polymers have different sensitivity to compressibility and surface roughness. The approach of using surface roughness to describe repeated micro-features was also validated experimentally by using an aluminium alloy 6061 insert with an array of micro-holes.